Desain Media Promosi Kopi Berbasis Photoshop (Studi Kasus : Cafe Kopi Koplak) - Sandi, Supriyadi (Jurnal Komunikasi, 2023)
Packaging design and brand image are two variables that help products attract customer attention. The research design involved data analysis and data collection methods through observation, interviews, and literature review. The findings of the Koplak Coffee Cafe study design use verbal and visual models with the aim of creating an effective packaging design both vocally and aesthetically. The packaging design process has produced label and packaging designs that utilize the Adobe Photoshop CS5 program. The aim of this final product design is to show how the adoption of new packaging increases the value of Kopi Kopi Koplak. describes how packaging design can help increase sales. Packaging design goals are very important to build brand reputation and make products more attractive to customers. Continuous packaging innovation should be used in the future, but some aspects of the original design should be retained in the latest version. This study shows that the packaging of Koplak Cafe Coffee has been designed to increase sales.